CONSUMER PROTECTION RELATED TO DISPENSING PUMP MANIPULATION IN SPBU (GAS STATION) - Deviana Yuanitasari; Sonny Dewi Judiasih; Ratu Chairunissa (UNISSULA, 2020)
Services in business activities at SPBU (gas station) often created problems between business operators and consumers that can cause cost to consumers. Underhanded practices are carried out by SPBU owner by manipulation digital technology systems that automatically measure the flow of fuel (dispensing pump) that is not in accordance with the measurements. This writing aims to review and analyze responsibility of business operators and legal protection for consumers related to manipulation dispensing pump of SPBU. The method used in this research is normative juridical with descriptive-analytical research specifications conducted with the approval of the regulations in the field of employment in terms of layoffs conducted by companies and research by interviewing the parties involved in industrial relations. Based on the research results obtained answers is: First, the responsibility of business operators who carry out manipulation dispensing pump is to revoke the PASTI PAS predicate within a period of two months and terminating cooperative relationship if the business operators is considered to inflict losses many consumers by Pertamina and granting compensation in accordance with Article 19 of UUPK. Second, legal protection for consumers is protection in the form of preventive and repressive, where prevention is carried out coaching by the government or Pertamina and repressive with law enforcement or settlement of consumer disputes both through the court and outside the court.